Обробка документів в інтегрованому середовищі Windows SharePoint Services - Гарбич-Мошора, Ольга (Видавництво Львівської політехніки, 2017)
The material presented in the article are important because of the need introduction of modern information technology in document management, which in turn is dniyeyu form of creating a developed information society. A method for forming and processing of documents in an integrated environment of Windows SharePoint Services - Microsoft Word.
Keywords: електронний документообіг; інформаційні технології